Comparative characteristics of semiconductor and metal thermocouples for thermoelectric power source - Mykytiuk, P.D.; Mykytiuk, O.Yu. (Journal of Thermoelectricity, 2024)
This work is devoted to the comparison of characteristics of semiconductor and metallic thermocouples for their use in thermoelectric generators, which is of great practical importance. The differences in the choice of thermoelectric material (TEM) for thermoelectric devices of different types are considered and the relationship between the main parameters of the thermoelectric power source and the properties of the TEM is shown. A comparison of the efficiency of semiconductor and metallic thermocouples is made based on the analysis of their physical characteristics.